Anorexia and inflammation: Food intake studies in a rat model of intestinal inflammation. - McHugh, James Kevin (My University, 1994)
This research examines the hypothesis that in rats inflammation of the gastrointestinal tract results in a specific decrease of food intake. A model for examining gastrointestinal inflammation, the trinitrobenzene sulphonic acid model, and its effects on feeding is developed and investigated in the rat. The TNB model results in a predictable and reproducible colonic inflammation that is accompanied by a rapid but transient decrease in food intake. Experiments are presented which: i)investigate if the anorexia is due to nonspecific malaise. ii)investigate, by meal pattern analysis, the profile of food intake displayed by TNB treated animals iii)investigate specifically, which mediators released from the sight of inflammation could be an anorexigenic signal to the central nervous system.
To demonstrate that the anorexia is not due to malaise we have shown that the anorexia: is not specific to the TNB model, is accompanied by no decrease in water intake and develops even when animals are maintained on highly palatable or low residue liquid diets. More importantly animals specifically decrease meal size not meal frequency. Decreased meal size with maintenance of meal frequency is consistent with the generation of abnormal satiety signals and not a "general malaise." These findings show that rats are capable of performing the behaviours necessary for food intake, and do not show specific conditioned taste aversions.
The hypothesis that the generation of abnormal gastric and/or post-gastric satiety signal is responsible for TNB induced anorexia was also investigated. I demonstrated removal of both gastric and post-gastric satiety signals in a sham feeding preparation resulted in normal intake even in otherwise anorexic animals. I also show that animals with TNB induced colonic inflammation, present with a decreased rate of gastric emptying. These data raise the possibility that abnormal satiety signals, generated as a result of decreased gastric emptying result in decreased meal size and an overall anorexia.
Finally, by specifically inhibiting synthesis of leukotrienes and prostaglandins respectively, or by using an interleukin-1 receptor antagonist (rhIL-1ra), I examined the role of these inflammatory mediators in the anorexia seen in the TNB model of colitis in the rat. I demonstrate that inhibition of prostaglandin synthesis and blockage of interleukin-1 receptors particularly in the brain, result in a significant attenuation of the anorexia. I conclude that the full expression of the anorexia observed in TNB treated animals is dependant on the production of prostaglandins and occupation of centrally located interleukin-1 receptors. Thus, here I specifically describe a model suitable for the investigation of the mechanisms of gastrointestinal inflammation induced anorexia and generally a model that may be used to examine how peripherally generated signals can alter behaviour by communication with the central nervous system.
Keywords: Medical Sciences; Medical Sciences